The Sanjak of Alexandretta (Hatay) in Turkish Foreign Policy: A Case of “Accidental Diaspora” and Kin-State Politics - PAPUÇÇULAR, HAZAL (Palgrave Macmillan, 2020)
This chapter deals with the place of the Sanjak Turks in the formulation and implementation of Turkish foreign policy toward the Sanjak of Alexandretta—as later called Hatay—in the interwar period. Utilizing the concept of “accidental” diaspora, which indicates a kin-group that comes into existence because of the dissolution of the empires, it analyzes the policies of Turkey over this community. It shows that the collaboration between Ankara and the Sanjak Turks dated back to the Turkish War of Independence and intensified in the mid-1930s. It argues that Ankara’s aim to annex the region turned the Turkish community into a crucial element of Turkish foreign policy and led to identity-based policies targeting the Sanjak Turks. This chapter searches the possibilities of employing a transnational approach to an interwar foreign policy case, which has usually been analyzed by traditional historical narratives.
Keywords: Sanjak Turks; Turkish foreign policy